2014
DOI: 10.1063/1.4901994
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependent lattice dynamics in MoSxSe(2–x) alloys

Abstract: We report on room temperature, polarization-resolved Raman scattering measurements on layered crystals of the series MoSxSe(2–x) (0 ≤ x ≤ 2) grown by chemical vapor transport technique. The results reveal two distinct sets of features related to the E2g1 and A1g modes of pure members of series. As composition x changes, the in-plane E2g1 mode shows two-mode behavior, whereas the out-of-plane A1g mode presents more complex evolution. The MoSe2-like branch reveals the splitting associated with the altering arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…24,25 Figures 4a and 4b show the optical image and the composite PL map, respectively, of a threejunction lateral heterostructure composed of monolayered alloys (MoS2(1-x)Se2x -WS2(1-x)Se2x -MoS2(1-x)Se2x -WS2(1-x)Se2x), These were grown in a sequence of 12-0.3-3-0.7 min; via a similar carrier gas switching procedure using a mixture of MoS2 and WSe2 as the solid source. The sequential morphology observed in this case is close to conformal, indicating that the growth rate for each material in the heterostructure is isotropic (Extended data Fig.…”
mentioning
confidence: 99%
“…24,25 Figures 4a and 4b show the optical image and the composite PL map, respectively, of a threejunction lateral heterostructure composed of monolayered alloys (MoS2(1-x)Se2x -WS2(1-x)Se2x -MoS2(1-x)Se2x -WS2(1-x)Se2x), These were grown in a sequence of 12-0.3-3-0.7 min; via a similar carrier gas switching procedure using a mixture of MoS2 and WSe2 as the solid source. The sequential morphology observed in this case is close to conformal, indicating that the growth rate for each material in the heterostructure is isotropic (Extended data Fig.…”
mentioning
confidence: 99%
“…Among mixed Se-S branch, we can identify at least three components, shifting to higher frequency upon increasing y. They are well resolved for 0.1 < y < 0.2, when the 2Se 2 + 1SeS, 2Se 2 + 1S 2 or 1Se 2 + 2SeS arrangements are the most probable [33][34][35][36]. By contrast, Se-Se branch shifts to lower frequency.…”
Section: Resultsmentioning
confidence: 88%
“…In MoS 2 the A 1 phonon energy of 51 meV [33] strongly exceeds those in MoSe 2 . For that reason incorporation of sulfur atoms into MoSe 2 host lattice results in significant increase of the A 1 phonon energy [36]. We found that the high temperature trion to exciton PL intensity ratio (I T /I X ) increase with sulfur mole content.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations